Management of T‐cell malignancies: Bench‐to‐bedside targeting of epigenetic biology - Ariana Sabzevari; Johnson Ung; Jeffrey W. Craig; Kallesh D. Jayappa; Ipsita Pal; David J. Feith; Thomas P. Loughran; Owen A. O’Connor (CA: A Cancer Journal for Clinicians, 2025)
Abstract The peripheral T‐cell lymphomas (PTCL) are the only disease for which four histone deacetylase (HDAC) inhibitors have been approved globally as single agents. Although it is not clear why the PTCL exhibit such a vulnerability to these drugs, understanding the biological basis for this activity is essential. Many lines of data have established that the PTCL exhibit marked sensitivity to other epigenetically targeted drugs, including EZH2 and DNMT3 (DNA‐methyltransferase 3) inhibitors. Even more compelling is the finding that combinations of drugs targeting the epigenetic biology of PTCL are beginning to produce provocative data, leading some to wonder if these agents can replace historical chemotherapy regimens routinely used for patients with the disease. Simultaneously, the field has identified a spectrum of mutations in genes governing epigenetic biology in many subtypes of PTCL, although the T follicular helper lymphomas, including angioimmunoblastic T‐cell lymphoma, appear to be particularly enriched for these genetic features. While the direct relationship between the presence of any one of these mutations and responsiveness to a particular epigenetic drug has yet to be established, it is increasingly accepted that the PTCL may be the prototypical epigenetic disease as no other form of cancer has exhibited such a vulnerability to this diversity of epigenetically targeted agents. Herein, we comprehensively review this esoteric and rapidly evolving field to identify themes and lessons from these experiences that may guide efforts to improve outcomes of patients with T‐cell neoplasms. Furthermore, we will discuss how these concepts might be applied to the broader field of cancer medicine.